STROKE AND THROMBOLYTIC THERAPY AWARENESS AMONG MEDICAL STUDENTS: A CROSS-SECTIONAL STUDY AT DAI NAM UNIVERSITY, VIETNAM (Vietnam Journal of Community Medicine, 2026)
Background: Stroke is a critical global health issue, consistently ranking as a leading cause of mortality and long-term disability. In Vietnam, while stroke units have expanded, public awareness and the timely use of advanced therapies remain significant challenges. This study aims to assess the awareness regarding stroke and thrombolytic therapy among medical students at Dai Nam University in 2024.Methods: A cross-sectional descriptive study was conducted from November 2024 to March 2025 at Dai Nam University, Hanoi. Data were collected through a self-administered structured questionnaire. Descriptive statistics and SPSS version 25.0 were used for data analysis, with the Chi-square test employed to compare between pre-clinical and clinical groups.Results: Among 228 medical students in the study, a vast majority of participants (97.4%) had previously heard of stroke, but only 46.1% were aware of thrombolytic therapy. Clinical students demonstrated significantly higher proficiency in identifying risk factors and warning signs, such as limb weakness (93.9%) and facial deviation (93.1%), compared to pre-clinical students (p < 0.05). Notably, only 19.7% of the total sample correctly identified the 4.5-hour "golden hour" window for thrombolysis. While 72.8% of students chose immediate emergency transport as the primary action, a small proportion (6.1%) still favored unscientific traditional practices.Conclusion: The study highlights a substantial gap between general stroke awareness and specific knowledge of emergency interventions among medical students. While clinical training significantly improves symptom recognition, there is a need to enhance education regarding the time-sensitive nature of thrombolytic therapy. These results emphasize the necessity of updating medical curricula to include more focused training on acute stroke protocols and the 4.5-hour treatment window to improve future stroke care in Vietnam.
Keywords: Stroke, Thrombolysis, Awareness, Medical Students, Dai Nam University.